Pemberian Marga dalam Perkawinan adat Mandailing - Sugiarto, Ucok (Jurnal El-Thawalib, 2022)
This research is motivated by the practice of giving clans in Mandailing traditional marriages in Kotasiantar village before carrying out traditional marriage ceremonies in order to carry out traditional marriages. The formulation of the research problem is how is the process of giving clans in Mandailing traditional marriages, what are the factors and functions of clans in Mandailing traditional marriages and the last is what is the view of Islamic law on giving clans in Mandailing traditional marriages.The clan is born when a family forms a group or forms a village. With the birth of this clan, each of its descendants will continue to use the same clan. In other words, the father's clan will be passed down to his son (Patrilineal). In the Mandailing custom, the clan can be given to someone who is not from the Mandailing tribe for reasons of devotion, respect and marriage.This research is a field or qualitative research, namely research conducted with an approach that is oriented towards observed phenomena and processed using scientific logic. This type of research uses descriptive qualitative, the data source in this study uses primary and secondary data.From the results of this study, it can be concluded that the process of giving the clan in Mandailing traditional marriages is very necessary to carry out traditional marriages. The factor and function of giving a clan in a traditional Mandailing marriage is that the factor can give the clan given to him to his descendants, and its function is to get the title of harajaon. Then the view of Islamic law on the process of giving the clan may be because it does not conflict with Islamic law.